A survey on perception and knowledge of transfusion medicine among final year medical students - Muhammad, Siti Aeshah @ Naznin; A.Talib, Norlelawati; Abdullah, Nor Zamzila; Jantan, Abdul Wahab (2009)
Acquisition of knowledge and good skills in transfusion medicine by undergraduate curriculum. The subsequent clinical practice in transfusion medicine upon graduation is partly influenced by the training received in medical schools. As such the training during the clinical years should be an important element of medical undergraduate teaching.1 In IIUM the science about transfusion medicine is dealt with in the preclinical years, namely in the haematology and the immunology blocks. The teaching learning methods adopted are large group teaching(lecture), tutorial, practical and problem-based learning (PBL) sessions. In the clinical years there is no designted module fir transfusion medicine. It is incorporated into the various clinical postings with formal sessions (lectures and seminars) being conducted namely in urgical and anaesthesiology postings. As for other postings, learning transfusion medicine is part of the ward-based activities. In the preclinical years transfusion medicine is assessed through multiple true-false questions, short-notes, essay, objectively structured practical exam and problem-based questions. In the clinical years assessment related to transfusions, patient management problem and long and short case examinations. The objective of this survey was to assess the perception of final year medical students of the International Islamic University Malaysia(IIUM) about transfusion medicine curriculum input and their knowledge in the core areas of transfusion medicine upon graduation.